MODERNISASI TRANSPORTASI DAN MOBILITAS EDUKASI DI KARESIDENAN KEDIRI (1830–1870): SEBUAH KAJIAN HISTORIS - Siti Musa’adah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The modernization of transportation in Kediri (1830–1870) was primarily driven by colonial economic interests, specifically the Cultivation System and the sugar industry. However, its impact extended beyond economics, significantly influencing social dynamics, including educational mobility. This study aims to analyze the development of transportation infrastructure and its impact on educational mobility in the Kediri Residency during the 1830–1870 period. Using historical methods comprising heuristics, source criticism, interpretation, and historiography, this research examines colonial records, infrastructure reports, and educational documents. The results indicate that the construction of the Groote Postweg, the optimization of the Brantas River routes, and the early introduction of rail networks, although intended for sugar distribution, inadvertently facilitated educational mobility. Improved infrastructure allowed for the movement of colonial school inspectors, teachers, and a limited number of indigenous students accessing formal education. Furthermore, it accelerated the circulation of educational materials and modern ideas into the Kediri interior. Thus, transportation modernization served as a crucial, albeit unintended, catalyst for the early expansion of educational access and mobility in the region.